A Biblical Principle-Based Model of Christian Education Management in the Church Context in the Digital Era - Agustina, Eunike (Jurnal Didaskalia, 2025)
Digital transformation has reshaped the paradigm of educational management, including within the context of the church. However, the implementation of Christian education management in churches continues to face challenges in integrating biblical principles with the demands of digitalization. This study aims to formulate a Christian education management model that integrates biblical principles with digital technology within the context of church ministry. The research adopts a qualitative approach using a literature review method, analyzing theological, educational management, and digital technology literature published between 2020 and 2024. The study results in a Christian education management model comprising five key dimensions: (1) an organization grounded in biblical principles that integrates design, leadership, and administrative aspects; (2) an adaptive organizational structure tailored to church size and age-group segmentation; (3) a learning approach relevant to the digital cultural context; (4) the digitalization of management through virtual communities, digital learning platforms, and church information systems; and (5) continuous evaluation based on Christian values. The resulting model offers a comprehensive framework that preserves theological integrity while leveraging digital technology to enhance the effectiveness of Christian education within the church.